THE ROLE OF SELF-REWARD IN BOOSTING PERFORMANCE AND MENTAL WELL- BEING FOR REMOTE GENERATION Z WORKERS - Defalia Widamutia; Veithzal Rivai Zainal; Azis Hakim (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Generation Z, as digital natives, possess unique characteristics that make them susceptible to stress and burnout. This study aims to explore the impact of self- reward on the performance and mental well-being of Generation Z employees working remotely. Specifically, this research investigates how self-reward can serve as an effective coping mechanism for Generation Z in dealing with high job demands and social isolation associated with remote work. Through a qualitative descriptive approach, this study analyzes the subjective experiences of Generation Z employees regarding their characteristics related to the implementation of self-reward. The findings indicate that self-reward not only enhances performance and motivation but also plays a significant role in maintaining emotional balance and reducing stress levels. Additionally, this study identifies the most effective types of self-reward for Generation Z and the factors influencing the success of its implementation. These findings have important implications for organizations in designing more effective employee development and well-being programs.